Real-life relevant face perception is not captured by the N170 but reflected in later potentials: A comparison of 2D and virtual reality stimuli - Sagehorn, Merle; Johnsdorf, Marike; Kisker, Joanna; Sylvester, Sophia; Gruber, Thomas; Schöne, Benjamin (Frontiers in Psychology, 2023)
The perception of faces is one of the most specialized visual processes in the human brain and has been investigated by means of the early event-related potential component N170. However, face perception has mostly been studied in the conventional laboratory, i.e., monitor setups, offering rather distal presentation of faces as planar 2D-images. Increasing spatial proximity through Virtual Reality (VR) allows to present 3D, real-life-sized persons at personal distance to participants, thus creating a feeling of social involvement and adding a self-relevant value to the presented faces. The present study compared the perception of persons under conventional laboratory conditions (PC) with realistic conditions in VR. Paralleling standard designs, pictures of unknown persons and standard control images were presented in a PC- and a VR-modality. To investigate how the mechanisms of face perception differ under realistic conditions from those under conventional laboratory conditions, the typical face-specific N170 and subsequent components were analyzed in both modalities. Consistent with previous laboratory research, the N170 lost discriminatory power when translated to realistic conditions, as it only discriminated faces and controls under laboratory conditions. Most interestingly, analysis of the later component [230-420 ms] revealed more differentiated face-specific processing in VR, as indicated by distinctive, stimulus-specific topographies. Complemented by source analysis, the results on later latencies show that face-specific neural mechanisms are applied only under realistic conditions (video abstract: https://youtu.be/TF8wiPUrpSY).